Correction: Lai et al. Sensitivity Enhancement of Group Refractive Index Biosensor through Ring-Down Interferograms of Microring Resonator. Micromachines 2022, 13, 922 - Hsuan Lai; Tzu-Ning Kuo; Jia-Yi Xu; Shih-Hsiang Hsu; Yi-Cheng Hsu (Micromachines, 2022)
In the original publication [...]